HOMEIRA QADRI’S DANCING IN THE MOSQUE (2020): REPRESENTING CULTURAL NORMS IN CONSTRUCTING GENDER STEREOTYPES - Mohammadi, Noria; Rahayu, Lina Meilinawati; Saleha, Amaliatun (Metahumaniora, 2024)
Homeira Qaderi’s memoir, Dancing in the Mosque (2020), portrays how cultural norms construct gender expectations and perpetuate stereotypes. Using a dual narrative structure that intertwines Shah Pesar’s magical adventures with Qaderi’s poignant reflections illustrates how Qaderi skillfully employs focalization to shed light on the cultural limitations imposed on Afghan women, blending realistic storytelling elements. This study utilizes Bal’s theory of focalization alongside Genette’s concept of zero focalization to analyze the narrative shift from an omniscient narrator to a first-person perspective. By applying these theories, we examine how the shift in perspective highlights emotional intricacies and sharp feminist critique, while also revealing the narrative control and the lens through which the characters’ experiences are portrayed. We investigate the marginalization of women through the issues of constrained mobility, loss of identity, and legal disenfranchisement. By centering on Qaderi’s perspective, the text critiques societal and legal structures that diminish women’s value while foregrounding their struggle for agency and self-definition in a patriarchal society. This study underscores the broader ramifications of gender narratives in Afghanistan, highlighting the resilience of women as they resist cultural suppression.